(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lianah L, Kusumarini N, Hafshah M, Krisantini K, Kurniawati A, Ahmad MA. 2023. Chemical characterization of mint (Mentha spp.) germplasm from Central Java, Indonesia. Biodiversitas 24: 4307-4313. The main objective of this work was to evaluate and compare the leaf production and oil content of the four mint genotypes (Mentha spp.) from Central Java, Indonesia. Four genotypes were collected from Rejosari Village, Kudus District, Central Java, Indonesia, namely spearmint (Mentha spicata), peppermint (Mentha x piperita), orange mint (Mentha x piperita ‘Orange’) and chocolate mint (Mentha x piperita ‘Chocolate’). Essential oil extraction was carried out by steam distillation. Identification of the chemical compounds of the oil and their relative percentage were analyzed using GC-MS. Leaves productivity ranged between 500-1000 kg/ha, and essential oil content from 0.4 to 1.36%. The major essential oil constituents detected were 1,8-cineole, carvone, limonene, linalool, linalyl acetate, menthol, menthone, menthyl acetate, and piperitenone oxide. Chocolate mint had the highest leaf production and the highest content of essential oil (4.17%) and menthone yield (28%) compared to the other genotypes.